DA AMOSTRAGEM À PURIFICAÇÃO: METODOLOGIAS E TÉCNICAS PARA AVALIAÇÃO DE SILOXANOS NO BIOGÁS - Carla M. B. Gomes; Cleuciane T. do Nascimento; Rodolfo A. Schaffner; Guilherme E. Q. Souza; Alessandra Freddo; Daiana G. Martinez; Helton J. Alves (Química Nova)
FROM SAMPLING TO PURIFICATION: METHODOLOGIES AND TECHNIQUES FOR EVALUATION OF SILOXANES IN BIOGAS. Biogas has emerged as an important source of clean and renewable energy, with its energy viability dependent on purity grade. Primarily composed by methane and carbon dioxide, biogas can also contain nitrogen, water vapor, oxygen, hydrogen sulfide, ammonia, hydrocarbons and siloxanes. Regarding methane, all other components are considered contaminants, with volatile methylsiloxanes (VMSs) being the major challenge in terms of control and removal. VMSs are commonly found in personal care products and industrial applications, and their presence is highly detrimental to biogas energy generation equipment by forming silica deposits that cause fouling and damage, reducing operational efficiency and system longevity. In this context, three topics are crucial: (i) sampling techniques (bags, gas cylinders, canisters, adsorbent tubes, and impingers); (ii) detection and quantification methods for VMSs, highlighting gas chromatography coupled with mass spectrometry; and (iii) biogas purification/removal strategies (adsorption, absorption, refrigeration/condensation, biological degradation, and membrane separation). This review explores the methodologies involved in these topics, presenting literature research approaches and their effectiveness regarding siloxanes, contributing to biogas applications.